Seine Plastic Debris Transport Tenfolded During Increased River Discharge - van Emmerik, Tim; Tramoy, Romain; van Calcar, Caroline; Alligant, Soline; Treilles, Robin; Tassin, Bruno; Gasperi, Johnny (Frontiers in Marine Science, 2019)
Rivers transport land-based plastic waste into the ocean. Current efforts to quantify riverine plastic emission come with uncertainty as field observations are scarce. One of the challenging aspects is the lack of consistent measurement methods that allow for comparing rivers over space and time. Recent studies have shown that simple visual observations provide a robust first-order characterization of floating and superficially suspended plastic transport, both in quantity, spatiotemporal distribution and composition. For this study, we applied this method to the river Seine, France, to provide new insights in the spatiotemporal variation in riverine plastic transport. First, we studied the response of plastic flow to increased river discharge by comparing measurements taken during low flow and high flow periods. Second, we investigated the variation of riverine plastic transport over the river length to improve our understanding of the origin and fate of riverine plastics. We demonstrate that during a period with higher river discharge, plastic transport increased up to a factor ten at the observation point closest to the river mouth. Upstream of Paris plastic transport increased only with a factor 1.5, suggesting that most plastics originate from Paris or areas further downstream. With this paper we aim to shed additional light on the seasonal variation in riverine plastic transport and its distribution along the river length, which may benefit future long-term monitoring efforts and plastic pollution mitigation strategies.